Analisis Sistem Pengelolaan Infrastruktur Persampahan Di Kabupaten Muna - Soeparyanto, Try Sugiyarto; Alamsyah, Sahrul; Mulawati, Mulawati; Yusran, Yusran (Departement of Civil Engineering, Universitas Winaya Mukti, 2025)
Suboptimal waste management has a direct impact on the environment and the quality of life of the community, especially in areas with high waste volumes. This condition requires more attention from the local government to immediately intervene in the form of infrastructure development, budget allocation, and increasing management capacity in sub-districts with high waste volumes. The purpose of this study was to analyze the Waste Infrastructure Management System in Muna Regency. This study is a qualitative and quantitative descriptive study. The data used are secondary data obtained from the Muna Regency Environmental Service. The data analysis method was used to describe the direction of the waste infrastructure management concept in Muna Regency. The analysis used to analyze the waste infrastructure management system in Muna Regency. Waste management in Muna Regency requires significant improvements in infrastructure, policies, and public education to create a more effective and sustainable system. By building important facilities such as waste banks, recycling centers, and organic waste management infrastructure, Muna Regency can reduce pressure on landfills while utilizing the economic potential of waste. Strong regulatory support, cross-sector collaboration, and the use of technology are also important factors in optimizing waste management and creating a sustainable circular economy.